Fluorogenic Bifunctional trans‐Cyclooctenes as Efficient Tools for Investigating Click‐to‐Release Kinetics. Issue 44 (3rd June 2020) - de Geus, Mark A. R.; Maurits, Elmer; Sarris, Alexi J. C.; Hansen, Thomas; Kloet, Max S.; Kamphorst, Kiki; ten Hoeve, Wolter; Robillard, Marc S.; Pannwitz, Andrea; Bonnet, Sylvestre A.; Codée, Jeroen D. C.; Filippov, Dmitri V.; et al.
Abstract: The inverse electron demand Diels–Alder pyridazine elimination reaction between tetrazines and allylic substituted trans ‐cyclooctenes (TCOs) is a key player in bioorthogonal bond cleavage reactions. Determining the rate of elimination of alkylamine substrates has so far proven difficult. Here, we report a fluorogenic tool consisting of a TCO‐linked EDANS fluorophore and a DABCYL quencher for accurate determination of both the click and release rate constants for any tetrazine at physiologically relevant concentrations. Abstract : Click‐to‐release ! A new fluorogenic trans ‐cyclooctene probe was has been designed and synthesized to determine the elimination kinetics of the click‐to‐release reaction. The reagent enables accurate detection of the decaging potential for any tetrazine at physiologically relevant concentrations.